KARBON AKTIF DARI SEKAM PADI : PEMBUATAN DAN KAPASITASNYA UNTUK ADSORPSI LARUTAN ASAM ASETAT - Hesti Wijayanti (Universitas Lambung Mangkurat, 2009)
Activated carbons prepared from rice husks, an agricultural waste by product, have been examined for the removal of acetic acid from aqueous solutions. The activated carbon was prepared by physical activation. The results show that the Freundlich isothem model were well fitted rather than Langmuir model. They also indicate that the sorption of acetic acid is depend on the stirrer velocity as well as on the particle size of the activated carbons.